The girl from Scotland Yard - Wallace, Edgar, 1875-1932 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Girl from Scotland Yard" by Edgar Wallace is a detective novel written in the early 20th century. It centers on a poised young investigator, Leslie Maughan, who probes a tangle of high-society secrets involving Lady Raytham, her bullying confidante Princess Anita Bellini, and a newly freed ex-convict, Peter Dawlish. A menacing butler, a suspicious cash withdrawal, and a murder tied to an emerald necklace pull police and aristocrats into the same web. The opening of the novel shows Lady Raytham on edge as friends visit and talk turns to Peter Dawlish, recently released after a notorious forgery case. Leslie Maughan arrives from Scotland Yard to question Lady Raytham about a large, sudden withdrawal, rattling her further. That night Leslie encounters Peter on the Embankment, challenges his self-pity, and helps him toward a fresh start; he is soon assaulted by three small, silent attackers but survives and finds shabby lodgings. Meanwhile Druze, the butler, behaves erratically; later, Leslie and Chief Inspector Coldwell come upon Druze$1 (Bs corpse on Barnes Common, shot and clutching a square emerald. Leslie follows a trail of searched belongings (passport, New York ticket, a stuffed wallet) and bare footprints, then confronts Lady Raytham, whose emerald chain is somehow intact despite a matching pendant found in the dead man$1 (Bs hand. Pressed about her movements, Lady Raytham admits she discovered the body and collapses when Peter$1 (Bs name is mentioned, setting the core mystery and suspects in motion. (This is an automatically generated summary.)s
Release date is 2025-08-12
an anonymous Project Gutenberg volunteer
Keywords: Detective and mystery stories; Police -- Great Britain -- Fiction; Women detectives -- Fiction